2012
DOI: 10.1016/j.rasd.2011.06.014
|View full text |Cite
|
Sign up to set email alerts
|

Dietary patterns and body mass index in children with autism and typically developing children

Abstract: To determine whether dietary patterns (juice and sweetened non-dairy beverages, fruits, vegetables, fruits & vegetables, snack foods, and kid’s meals) and associations between dietary patterns and body mass index (BMI) differed between 53 children with autism spectrum disorders (ASD) and 58 typically developing children, ages 3 to 11, multivariate regression models including interaction terms were used. Children with ASD were found to consume significantly more daily servings of sweetened beverages (2.6 versus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
100
0
7

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 155 publications
(114 citation statements)
references
References 39 publications
7
100
0
7
Order By: Relevance
“…medication use, cognitive impairments, eating problems) (14)(15)(16) . Compared with typically developing peers, youth with I/DD, including children with autism spectrum disorder, consume fewer daily servings of fruits and vegetables (17,18) and these outcomes have a positive association with lower family income (18) . Schools represent ideal environments for public health interventions to improve population-level dietary patterns of children and adolescents (19) .…”
mentioning
confidence: 99%
“…medication use, cognitive impairments, eating problems) (14)(15)(16) . Compared with typically developing peers, youth with I/DD, including children with autism spectrum disorder, consume fewer daily servings of fruits and vegetables (17,18) and these outcomes have a positive association with lower family income (18) . Schools represent ideal environments for public health interventions to improve population-level dietary patterns of children and adolescents (19) .…”
mentioning
confidence: 99%
“…Several studies have reported that food selectivity may contribute to obesity in children with ASD [10]. Obesity is estimated to have a prevalence rate of 30% in children with ASD compared to 24% of their typically developing peers [11,12].…”
Section: Food Selectivity In Obese Adolescents With Autism Spectrum Dmentioning
confidence: 99%
“…Two longitudinal studies have shown that children with ASD have continued with similar food selectivity years later and in one case, decreased food repertoire [3,4]. Previous research has focused on children with ASD and food selectivity with mean ages ranging from four to eight years [1][2][3][4]7,10,13] with few addressing adolescents exclusively. Clearly, there exists a need to investigate food selectivity in adolescents with ASD.…”
Section: Food Selectivity In Obese Adolescents With Autism Spectrum Dmentioning
confidence: 99%
“…Children with ASD consume significantly more servings of juice and sweetened non-dairy beverages and snacks foods and significantly fewer servings of vegetables compared to typically developing children [10]. Some of the consistent factors in the food selectivity relate to food textures, color and flavor.…”
Section: Physical Status and Feeding Behavior Of Children With Autismmentioning
confidence: 99%